Geotechnical design for underground mining of stopes in narrow veins - Ramos Armijos, Nelson Jesús (2024)
The ore deposits in Ecuador are associated with narrow veins whose rock host is influenced by joints and stress that are sources of weakness, which needs to be studied for safe underground exploitation. Therefore, the objective of this research is to elaborate the geotechnical design for the underground mining stope in a narrow vein. For this purpose, the rocky massif was characterized using geomechanical classifications and its stability by means of Mathews' Graph. In addition, stress field, displacements and strength factor were examined using the failure criterion and RS2 software; additionally, the support was designed based on the quality of the rock mass and the mining method’s sequence. The results indicate that the maximum size of the stope is 54.00 m height, 1.75 m width, 79.00 m length; and, the designed support has stabilized the drifts. Also the results reveal that joints control the distribution of stress causing a decrease in these and strength of rock mass deteriorates; whereas, stability stope decreases as its depth increases, conversely, the thickness of plastic zone increases with such an increase and the displacement isn’t influenced by the depth of stope undercutting.